On-demand synthesis of phosphoramidites - Alexander F. Sandahl (Nature Portfolio, 2021)
The poor bench stability of phosphoramidites is a drawback for fast automised chemical oligonucleotide synthesis. Here, the authors report a method for on-demand flow synthesis of phosphoramidites within short reaction times, in near-quantitative yields and sufficient purity for integration with DNA synthesizers.